ANALYSIS OF THE EFFECT OF COARSE AGGREGATE PARTIAL SUBSTITUTION WITH GRANITE FRAGMENTS IN THE COMPOSITION OF CONCRETE MIXTURE MATERIALS TOWARD CONCRETE COMPRESSIVE STRENGTH - Wiyanti, Dwi Sri; Laksono, Taufik Dwi (International Journal of Engineering Technologies and Management Research, 2024)
The concrete basic composition can be modified by using alternative materials for coarse aggregate, fine aggregate, or modifying the type of sand. In this study, destructive method testing was applied to find the compressive strength of concrete that was mixed with coarse aggregate admixture material from granite waste that was combined with natural aggregate and then compared with normal concrete. The sands added to the mixture originated from the Serayu River and Mount Merapi. To create concrete with a planned quality of fc’ 30 Mpa, three types of test objects are created. The first is unmixed concrete (0% admixture), the second and the third are uses granite waste as coarse aggregate substitution as much as 50%, and 100%. The test objects were then tested for compressive strength in 7 days and 28 days. The seven (7) days test showed that maximum compressive strength of 22,23 Mpa was produced by a mixture of Mount Merapi and coarse aggregate substitution of 50% granite waste. The use of Mount Merapi sand and Serayu River sand in all substitution compositions of granite waste shows that concrete compressive strength that uses Mount Merapi sand is better than in the mixture that uses Serayu River sand.